Advances in Acoustic Emission Technology Proceedings of the World Conference on Acoustic Emission-2013 - Shen, Gongtian; Wu, Zhanwen; Zhang, Junjiao (Springer Proceedings in Physics, 2015)
This volume collects the papers from the 2013 World Conference on Acoustic Emission in Shanghai. The latest research and applications of Acoustic Emission (AE) are explored, with particular emphasis on detecting and processing of AE signals, development of AE instrument and testing standards, AE of materials, engineering structures and systems, including the processing of collected data and analytical techniques as well as experimental case studies.